Red blood cell membrane fatty acid composition in infants fed formulas with different lipid profiles - Visentin, Silvana Beatriz (2016)
BACKGROUND: There is growing interest in the fatty acid composition of breast milk and substitute formulas used to replace or complement infant breastfeeding. AIM: The aims of this study were to assess the impact of two follow-up infant formulas based on cow milk fat, vegetable oils and different docosahexaenoic (DHA) and arachidonic (ARA) acid content on red blood cell membrane fatty acid composition, and determine the percent saturated fatty acid (SFA) incorporation into the membrane. STUDY DESIGN: This was a double-blind, randomized, controlled, parallel-group clinical trial. Infants received treatment or control product for at least four months before the age of six months. The control group (n=25) received standard infant formula (FA) and the treatment group (n=24) received the same formula supplemented with higher DHA and ARA content (FB). The reference group (n=47) consisted of normal healthy exclusively breastfed infants. OUTCOME MEASURE: Red blood cell membrane fatty acid composition was determined by capillary gas chromatography. RESULTS: Ninety-six infants completed the study (FA, 25; FB, 24; reference, 47). Higher DHA content reflected higher DHA percentage in the red blood cell membrane. Breast milk and FB did not show any significant differences in DHA content. ARA percentage was higher in breastfed infants and palmitic acid percentage was higher in FB- compared with FA-fed infants. CONCLUSION: DHA and palmitic acid percent distributions were higher in the red blood cell membrane of infants receiving FB. DHA percent distribution was not significantly different in FB-fed and breastfed infants. SFA percent distribution was not significantly different when comparing both formulas with breast milk.